2011
DOI: 10.1002/pd.2699
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of abnormal cardinal systemic venous return without other heart defects: a case series

Abstract: Isolated ASVRs can be accurately diagnosed prenatally and are frequently associated with extracardiac and genetic anomalies. A detailed morphological ultrasound and fetal karyotype should be suggested. Neonatal outcome was mainly related to the associated anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
2
24
1
Order By: Relevance
“…A total of 2708 articles were identified, of which 64 full‐text articles were assessed for their eligibility for inclusion (Appendix S2). A total of 13 studies were included in the systematic review (Figure ). These 13 studies included 501 fetuses with PLSVC; of these, 37.3% (95% CI, 33.1–41.7%; 187/501) were isolated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2708 articles were identified, of which 64 full‐text articles were assessed for their eligibility for inclusion (Appendix S2). A total of 13 studies were included in the systematic review (Figure ). These 13 studies included 501 fetuses with PLSVC; of these, 37.3% (95% CI, 33.1–41.7%; 187/501) were isolated.…”
Section: Resultsmentioning
confidence: 99%
“…CHD, congenital heart disease; echo, echocardiography; GA, gestational age at diagnosis; NS, not stated; Prosp, prospective; Retro, retrospective. 32 Esmer (2014) 31 Du (2014) 30 Jowett (2012) 29 Barrea (2011) 28 Rizzo (2008) 27 Galindo (2007) 15 Berg (2006) 14 Pasquini (2005) 13 Head (2005) 26 Chaoui (2003) 25 Machevin-Surugue (2002) 24 Rein (2000) 23 Only the first author of each study is given. A study can be awarded a maximum of one star for each numbered item within the selection and outcome categories.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…However, the presence of PLSVC must be confirmed in the three-vessel view, because anomalous pulmonary venous drainage may also cause significant dilatation of the coronary sinus (8). Also, a dilated coronary sinus may be misdiagnosed as an ostium primum atrial septal defect at the level of the opening of the coronary sinus into the right atrium or as mitral atresia since the mitral valve is pushed anteriorly by the coronary sinus and may not be seen in the four-chamber view (7).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that cardiac defects themselves, but not PLSVC, were associated with an abnormal karyotype (2,6). On the other hand, chromosomal anomalies were present in five of the 15 fetuses with no additional cardiac defects in a recently published study by Barea et al (7). Moreover, one of these cases in which neonatal karyotyping revealed trisomy 21 had no associated extracardiac defect (7).…”
Section: Discussionmentioning
confidence: 99%
“…By gestational week 20, in normally developing embryo the left tube atrophies and blood flow is redistributed to the right side. The anatomical remnants are Marshall's ligament and vein coursing over the LA and marking the anatomical beginning of the CS, which ends in the RA [1,2,21]. The presence of PLSCV is a consequence of a lack of normal atrophy of the left anterior cardinal vein in the embryonic life.…”
Section: Discussionmentioning
confidence: 99%